RISK FACTORS OF TYPE 2 DIABETES MELLITUS DURATION AND NON-COMPLIANCE WITH MEDICATION TO POOR GLYCEMIC STATUS - Marisa Gita Putri; K. Heri Nugroho HS; Mateus Sakundarno Adi; Suhartono Suhartono; Bagoes Widjanarko (Universitas Airlangga, 2020)
Background: Type 2 diabetes mellitus is a chronic disease that is still a global health problem. Uncontrolled diabetes mellitus (DM) can result in poor glycemic status, with factors that affect patients including long-term DM and medication compliance. Purpose: This study aimed to determine the risk factors of long-term DM and non-compliance with medication on the poor glycemic control status of patients with type 2 DM. Methods: This type of research used observational analysis with a case–control design. Samples were taken from patients with type 2 DM, with 40 cases and 40 controls. The criteria for sample inclusion were that the patients had a glycosylated hemoglobin level check, were willing to be research respondents, and could communicate well. The exclusion criterion was patients experiencing a drastic decline in health status during the study. The sampling technique used was consecutive sampling. This research was conducted at the Panti Wilasa Citarum Hospital in Semarang City from July to September 2019. The relationship and the risk of long-term DM and adherence to taking medication with glycemic status were tested using the chi-square test. Results: This study showed that a duration of DM >5 years (p = 0.01; Odss Ratio (OR) = 3.46; 95% confidence interval [CI] = 1.37 < OR < 8.69) and non-compliance with taking medication (p = 0.02; OR = 3.15; 95% CI = 1.25 < OR < 7.93) are risk factors for poor glycemic status. Conclusion: Duration of DM >5 years and non-compliance with taking medication are risk factors for poor glycemic status in patients with type 2 DM.